Environmental Pollution Impact Analysis on Faecal Sludge Process Using Life Cycle Assessment and Analytic Hierarchy Process - Firlianda Imansyah; Nieke Karnaningroem (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2020)
The processing of fecal sludge in the IPLT is an advanced processing activity because the sludge in the septic tank has not been properly disposed of into the environment. After all, it still contains high organic loads. IPLT Kota Batu is the object of research. It aims to determine the environmental impact caused by the treatment of sludge in the IPLT Kota Batu with the Life Cycle Assessment Method then provide an alternative in reducing the impact with the Analytic Hierarchy Process Method. Life Cycle Assessment is a method for analyzing the environmental impact of a product throughout the life cycle. Stages of life cycle assessment (LCA) are goals and scope, life cycle inventory, life cycle impact assessment, and interpretation data. An alternative selection is then made to reduce the environmental impact using the Analytic Hierarchy Process (AHP) Method. AHP is describing a complex problem into a result that is represented in a multi-level structure. AHP stages are input goals, criteria, alternatives, weighting, and priority scale, producing the recommended answer or decision. From the LCA method, it was found that the emission load released into the environment in the treatment of sludge was in the form of CO2 emissions, energy emissions, and potentially disappearing species fractions of 3.948,935 kg CO2/year, 1.100.334,84 MJ, and 3.624,647 PDF.m2.y. The use of this method can find out that the treatment of sludge in the IPLT Kota Batu has an environmental burden and impacts the phenomenon of global warming, non-renewable energy, and aquatic eutrophication. The best alternative to reduce emissions in the treatment process of sludge in the IPLT Kota Batu is to perform maintenance treatment on a scheduled basis.